تجديد الخطاب الدعوي: ضروراته الشرعية ومشروعاته الإصلاحية: (Renewal of Da’wah Discourse (al-Khiṭāb al-Da’awī): Its Legitimate Necessities and Reform Projects) - عبد التواب مصطفى خالد معوض (At-Tajdid - Intellectual Refereed Journal, 2022)
The research discusses the idea between the appropriate concept of the renewal meaning of the dakwah discourse related to the emerging issues that need to be understood by the dakwah discourser, and explaines that the circle of the lawsuit discourse is not limited to rhetoric as claimed by some people; it includes the sermon, lesson, lecture, propaganda tape, book and brochure and fatwa, published in the social network. They also point out that the renewal of the propaganda discourse is required by the spirit of Islam, its general purposes and its legitimate duties, to fortify the faith of the Ummah and to protect its members from the phenomenon of excess and atonement and the destructive ideas carried by the intellectual invasion of the enemies to the ummah. They stressed that the renewal must be free from intolerance doctrine or worldly goals that distort religion. They focus on developing a reform programme for the renewal of religious discourse consisting of a reform programme for the individual himself, programmers related to the skill of the preachers and state-specific programmes towards preachers.The researcher recommends the necessity of renewing religious discourse at successive intervals, to follow the nation’s issues, to require the time, and to prepare workshops in which experts and specialists can participate; To review the curricula of colleges that graduate preachers, so that they are qualified for the preaching discourse and able to influence their listeners. It is like the pens that present images that belittle the preachers, or ridicule them in magazines, articles, and websites in all forms, and refute them and respond to them in a scientific manner away from emotions or intellectual fanaticism and doctrine, and establish a global association of preachers in which preachers exchange opinions, consultations, transfer of experiences, and raise moderation method. Keywords: Renewal, da’wah discourse, reform, necessity.